Penggunaan Internet di Kalangan Petani Talas dalam Memperoleh Informasi Pertanian pada Kelompok Tani Saluyu, Situgede, Bogor - Randy Fairuz Syauqi; Ninuk Purnaningsih (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
The number of internet users in Indonesia is increasing from year to year, But the use of the internet among farmers is still very minimal. This is caused by several constraints from internal farmers and farmer groups. Saluyu Farmer Group is one of the farmer groups located in Situ Gede Village, West Bogor, Bogor City. It is unfortunate that farmers who are members of the Saluyu Farmers Group receive little agricultural information from technology and informationbased media, especially the internet. This study aims to describe and analyze internet usage among taro farmers who are members of the Saluyu Farmers Group, Situgede. The research method was conducted using interviews with taro farmers as a guest speaker. The results showed that taro farmers who are membes of Saluyu farmers group are mostly old farmers and do not have the device to access the internet. This is caused by many factors, such as costs, income, knowledge, an the tendency of farmers to receive information from instructor. It can be concluded that farmers were more comfortable getting information directly compared to using media, such as the internet, because it feels cheaper and can be trusted. Key Word: Farmer, information, internet, technology